If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + 9 = 9 + -4b Reorder the terms: 9 + -3b = 9 + -4b Add '-9' to each side of the equation. 9 + -9 + -3b = 9 + -9 + -4b Combine like terms: 9 + -9 = 0 0 + -3b = 9 + -9 + -4b -3b = 9 + -9 + -4b Combine like terms: 9 + -9 = 0 -3b = 0 + -4b -3b = -4b Solving -3b = -4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4b' to each side of the equation. -3b + 4b = -4b + 4b Combine like terms: -3b + 4b = 1b 1b = -4b + 4b Combine like terms: -4b + 4b = 0 1b = 0 Divide each side by '1'. b = 0 Simplifying b = 0
| 2x^2+2y^2-8x+14y+26=0 | | .4x-2.1=.3 | | -3b+9=9-4bv | | -7b-5(8b+4)=24-3b | | 6(-5x+2)=-7 | | (x/4)+(1/6)=(x/7) | | -2(3t-2)+4t=3t-7 | | 6s+56.4=180 | | -9/2x+80=10 | | (X+.11x)+((30000-x)-1560+.04x)=990 | | 2w-16w=28 | | -9(x-1)-5x=-9+10(x+9) | | 24x=7x | | -9=y/3 | | c=b+bad | | 1+3(7p-7)=36+7p | | 5x^2+13x+2=0 | | -4(5t-5)+2t=8t-3 | | k/6= | | 39.5+8.74= | | -5(3x+1)=-30 | | 2y^2+7y+7/2 | | -25+15=m-9 | | .50x+.15(30)=44.5 | | -6+2n=6(n+3) | | -4(3t-4)+9t=3t-7 | | -6=b/16 | | 12(x+4)-4x=2(4x+4)-10 | | 4(2a-1)=20 | | 5x+7=2x-1 | | 5(h+3)=-25 | | n=a-k/5k |